2019
DOI: 10.3390/jcm8040432
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexual Dysfunction in Veterans with Post-Traumatic Stress Disorder

Abstract: Background: The problems in sexual functioning among patients with post-traumatic stress disorder (PTSD) are often overlooked, although scientific research confirms high rates of sexual dysfunctions (SD) particularly among veterans with PTSD. The main objective of this study was to systematically identify predictors of SD among veterans with PTSD. Methods: Three hundred veterans with PTSD were included in the cross-sectional study. The subjects were assessed by the Mini-International Neuropsychiatric Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 79 publications
0
27
1
Order By: Relevance
“…In these studies, sexual dysfunction was shown to be more frequent and more severe in veterans with PTSD symptoms (Antičević & Britvić, 2008; Hosain et al., 2013; Kotler et al., 2000; Letica‐Crepulja et al., 2019). In studies conducted by Crepulja et al and Anticevic et al, it was stated that avoidance, numbing and increased arousal, among PTSD symptoms, were particularly associated with sexual function problems (Antičević & Britvić, 2008; Letica‐Crepulja et al., 2019) The high level of anxiety, anger and irritability observed in these patients not only creates sexual dysfunction independently but also affects sexual dysfunction indirectly due to negative effects on social or romantic relationships and intimacy with the opposite sex (Gruden & Gruden Jr, 2000; Hosain et al., 2013; Kaplan, 1989) Moreover, the researchers reported that anger and anxiety might have a bidirectional relationship with erectile function. That is, anger and anxiety can create ED, and ED can induce or increase these symptoms (Kotler et al., 2000) The relationship between ED and psychological state has also been examined in large‐scale studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, sexual dysfunction was shown to be more frequent and more severe in veterans with PTSD symptoms (Antičević & Britvić, 2008; Hosain et al., 2013; Kotler et al., 2000; Letica‐Crepulja et al., 2019). In studies conducted by Crepulja et al and Anticevic et al, it was stated that avoidance, numbing and increased arousal, among PTSD symptoms, were particularly associated with sexual function problems (Antičević & Britvić, 2008; Letica‐Crepulja et al., 2019) The high level of anxiety, anger and irritability observed in these patients not only creates sexual dysfunction independently but also affects sexual dysfunction indirectly due to negative effects on social or romantic relationships and intimacy with the opposite sex (Gruden & Gruden Jr, 2000; Hosain et al., 2013; Kaplan, 1989) Moreover, the researchers reported that anger and anxiety might have a bidirectional relationship with erectile function. That is, anger and anxiety can create ED, and ED can induce or increase these symptoms (Kotler et al., 2000) The relationship between ED and psychological state has also been examined in large‐scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of suspected and confirmed cases, a heavy workload, a lack of protective equipment, a lack of specific medicines and poor psychological support may all increase the mental burden of HCP (Lai et al., 2020). Recent studies show that emotional numbness (emotional numbing) can prevent emotional intimacy and connectedness with a spouse, so PTSD symptoms can cause problems in sexual functions, and PTSD can be used as a predictive parameter for sexual dysfunction in these patients (Letica‐Crepulja et al., 2019). Many studies found that the prevalence of sexual dysfunction is higher in PTSD patients compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional abuse and neglect during childhood are recognized to often induce anxiety disorders and depression later in life, which are conditions closely connected with endometriosis [ 193 , 194 ]. PTSD impairs sexual functioning across multiple domains: desire, arousal, orgasm, activity, and satisfaction [ 195 , 196 , 197 , 198 ]. One logical conclusion is that sexual dysfunctions might lead to relationship troubles that have a consequential impact on affective stability and on the individual’s psychic structure.…”
Section: Neuropsychiatry and Endometriosis: The State Of The Artmentioning
confidence: 99%
“…A first study carried out in sample of 142 civilian war survivors showed women to report significantly higher levels of somatic symptoms than men, whereas levels of PTSD symptoms were similar in the two sexes (35). More recently, sexual dysfunctions, such as lack of sexual desire/pleasure or pain/problems during intercourse, have been reported in subjects exposed to trauma (36)(37)(38)(39), but limited data are available for PTSD civilian patients. In a literature revision, Yehuda et al (36) highlighted the comorbidity between sexual dysfunctions and PTSD in war veterans and proposed some biological and psychological underpinnings of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Another review including 11 articles on sexual dysfunctions in PTSD veterans showed that all but one study reported a significantly increased prevalence of sexual dysfunctions, especially erectile ones and decreased sexual desire ( 37 ). Finally, a recent study on 300 veterans with PTSD showed that sexual dysfunction was predicted by the severity of the D cluster of PTSD symptoms ( 39 ).…”
Section: Introductionmentioning
confidence: 99%